Continuous‐Flow Technology—A Tool for the Safe Manufacturing of Active Pharmaceutical Ingredients. Issue 23 (18th May 2015) - Gutmann, Bernhard; Cantillo, David; Kappe, C. Oliver
Abstract: In the past few years, continuous‐flow reactors with channel dimensions in the micro‐ or millimeter region have found widespread application in organic synthesis. The characteristic properties of these reactors are their exceptionally fast heat and mass transfer. In microstructured devices of this type, virtually instantaneous mixing can be achieved for all but the fastest reactions. Similarly, the accumulation of heat, formation of hot spots, and dangers of thermal runaways can be prevented. As a result of the small reactor volumes, the overall safety of the process is significantly improved, even when harsh reaction conditions are used. Thus, microreactor technology offers a unique way to perform ultrafast, exothermic reactions, and allows the execution of reactions which proceed via highly unstable or even explosive intermediates. This Review discusses recent literature examples of continuous‐flow organic synthesis where hazardous reactions or extreme process windows have been employed, with a focus on applications of relevance to the preparation of pharmaceuticals. Abstract : Go with the flow : Continuous‐flow processing is becoming increasingly important in synthetic organic chemistry. The high heat and mass transfer, very fast mixing, and small reactor volumes allow reactions to be run safely under very harsh conditions also when hazardous intermediates are involved, as shown here with selected examples.